SIRT5-mediated lysine desuccinylation impacts diverse metabolic pathways - Park, Jeongsoon; Chen, Yue; Tishkoff, Daniel X; Peng, Chao; Tan, Minjia; Dai, Lunzhai; Xie, Zhongyu; Zhang, Yi; Zwaans, Bernadette M M; Skinner, Mary E; Lombard, David B; Zhao, Yingming (Molecular cell, 2013)
Protein function is regulated by diverse posttranslational modifications. The mitochondrial sirtuin SIRT5 removes malonyl and succinyl moieties from target lysines. The spectrum of protein substrates subject to these modifications is unknown. We report systematic profiling of the mammalian succinylome, identifying 2,565 succinylation sites on 779 proteins. Most of these do not overlap with acetylation sites, suggesting differential regulation of succinylation and acetylation. Our analysis reveals potential impacts of lysine succinylation on enzymes involved in mitochondrial metabolism; e.g., amino acid degradation, the tricarboxylic acid cycle (TCA) cycle, and fatty acid metabolism. Lysine succinylation is also present on cytosolic and nuclear proteins; indeed, we show that a substantial fraction of SIRT5 is extramitochondrial. SIRT5 represses biochemical activity of, and cellular respiration through, two protein complexes identified in our analysis, pyruvate dehydrogenase complex and succinate dehydrogenase. Our data reveal widespread roles for lysine succinylation in regulating metabolism and potentially other cellular functions.